Preparation and Characterization of Biochar from Rice Straw and Its Application in Soil Remediation: DOI: 10.32526/ennrj.18.3.2020.27 - S. El-Hassanin, Adel; R. Samak, Magdy; R. Radwan, Soliman; A. El-Chaghaby, Ghadir (Environment and Natural Resources Journal, 2020)
In many developing countries, there is a large quantity of agricultural wastes that cause severe pollution problems. Also, the agricultural soils are polluted with heavy metals and there is a need to find an environmentally friendly approach for both getting rid of agro-wastes and helping in having more available soil for agriculture. In the present study, rice straw was used for the production of biochar for application in soil remediation. The biochar prepared by rice straw pyrolysis at 450 oC was characterized by different tools such as X-ray diffraction, Fourier-transformation infrared and scanning electron microscopy. The characterization results indicated that rice straw biochar (RSB) has amorphous porous structure with several functional groups and mainly composed of silicates. RSB was then investigated as soil remediating material for a silty clay soil. In this context, a synthetic polluted soil was prepared to contain 10 and 500 mg/kg of cadmium and lead, respectively. Rice straw biochar (RSB) was applied to the soil at the following (w/w) rates: 0% (control), 1.25% (T1), 2.50% (T2), 5.00% (T3) and 10.00% (T4). After 30 days of incubation, the soil samples were analyzed. The results showed that biochar addition resulted in a significant increase in soil pH, EC, CEC, total organic matter, total carbon and moisture. Application of biochar slightly increased the available N, P and K. The concentrations of plant available Pb and Cd in all biochar treatments were significantly lower than those of the control treatment. It can be concluded that biochar prepared from agricultural wastes is of both economic and environmental interest, especially in developing countries. Rice straw biochar could be further explored for remediating other types of soil pollutants with continuous monitoring of soil properties.